OPTIMALISASI SISTEM DROPSHIP DALAM JUAL BELI ONLINE PERSPEKTIF HUKUM ISLAM - Edy Imam Supeno; Ansari Ansari (NATUJA: Jurnal Ekonomi Syariah, 2024)
The online buying and selling dropship system is currently popular among the public. Buying and selling transactions in the dropship system involve suppliers, dropship sellers, and buyers. Dropship sellers acquire goods from suppliers and then sell them to consumers through social media platforms using technology. This study aims to identify the practice of dropship systems in online buying and selling transactions, as well as explore Islamic legal perspectives on the system in the context of online buying and selling transactions. Research methods that use library research are research approaches that rely on data sources from literature or written documents related to the object being studied. This method prioritizes the use of text and numerical data in the research process. Furthermore, this data is available in a ready-to-use form, without the need for additional processing. Furthermore, the condition of the data available within the library is not limited by space and time constraints. This study reveals that the practice of buying and selling transactions of the dropship system has fulfilled the provisions of the pillars of contract in a sharia perspective. In the perspective of Islamic law, it is legal and permissible to use the contract of greeting by complying with the terms and conditions applicable in the contract of greeting. To avoid gharar (uncertainty), a dropshipper must enter into an initial agreement with the supplier to guarantee and grant khiyar rights to the buyer to ensure the safety of the transaction and compliance with sharia principles in buying and selling.